PENGARUH KEPEMILIKAN MANAJERIAL DAN UKURAN PERUSAHAAN TERHADAP PERSISTENSI LABA PADA PERUSAHAAN JASA SEKTOR KEUANGAN YANG TERDAFTAR DI BEI TAHUN 2017-2021 - Rukmana, Risa; Saleh, Andi Mulia (Jurnal Akuntansi Kompetif, 2024)
The aim of this research is to determine the effect of managerial ownership and size on earnings persistence. The type of data used is quantitative data. The data source used is secondary data. The research population used was 107 financial sector services companies registered on the IDX in 2017-2021. The sampling technique in this research uses a purposive sampling technique based on certain criteria. Through the criteria applied, a sample of 23 financial sector service companies was selected. The analytical method used is simple linear regression with SPSS. The research results show that managerial ownership based on the partial test or t test has a significant and positive effect on earnings persistence. This is proven statistically with SPSS which shows a calculated t value of 3.105 > t table 1.983 and a significant value of 0.002 < 0.05. Based on this explanation, the hypothesis in this research is accepted. The research results show that company size based on the partial test has a significant and negative effect on earnings persistence. This is proven statistically with SPSS which shows a calculated t value of -2.260 < t table 1.983 and a significant value of 0.026 < 0.05. Based on this explanation, the hypothesis in this research is accepted